2014
DOI: 10.1111/jpim.12173
|View full text |Cite
|
Sign up to set email alerts
|

The Contributions of Firm Innovativeness to Customer Value in Purchasing Behavior

Abstract: The purpose of this research is to examine the influence of firm innovativeness and product innovativeness on the components of customer value mediated by instrumental and symbolic brand benefits.Over the last 10 years, the mobile phone industry in Korea has grown rapidly, with the introduction of several innovative phone features. The research context therefore is mobile phones with Internet access and their users in Korea.A major research finding is that the firm innovativeness affects product innovativeness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 62 publications
2
34
0
4
Order By: Relevance
“…In addition, cruise travellers' experience was found to have a significant positive effect on perceived luxury value. Kim et al (2015) also verified that perceived brand benefits (in instrumental and symbolic) through innovation enables mobile phone firms to create superior value for customers, which in turn can increase customer satisfaction.…”
Section: The Relationships Among Perceived Firm Marketing Innovation mentioning
confidence: 69%
See 2 more Smart Citations
“…In addition, cruise travellers' experience was found to have a significant positive effect on perceived luxury value. Kim et al (2015) also verified that perceived brand benefits (in instrumental and symbolic) through innovation enables mobile phone firms to create superior value for customers, which in turn can increase customer satisfaction.…”
Section: The Relationships Among Perceived Firm Marketing Innovation mentioning
confidence: 69%
“…Innovation allows differentiating the firm's offering by creating advantages that customers really appreciate and value (van Riel & Allard, 2012). Hence, the competitive advantage of successful firms can be explained with a logic wherein perceived firm marketing innovation initiatives (PFMII) contributes to customer value, resulting in increased satisfaction and behavioural intentions, eventually escalating loyalty that manifests itself in enhanced profitability (Kim et al, 2015;Kunz, Schmitt, & Meyer, 2011;Naidoo, 2010, Stock, 2011Williams & Soutar, 2009). More recently, Hwang and Hyun (2015) examined the role of perceived firm innovativeness based on data from 315 cruise travellers, and found that perceived firm innovativeness plays an important role in forming cruise travellers' experience related to education, entertainment, aesthetics, and escapism.…”
Section: The Relationships Among Perceived Firm Marketing Innovation mentioning
confidence: 99%
See 1 more Smart Citation
“…The theory of innovation as relevant brand value source in its actual meaning starts to be created later, when the influence of company innovativeness and product innovativeness on the components of customer value, is analysed [7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hypothesis H1: After the equation (1) substitution, the value of testing characteristic was calculated (7,325). The critical testing characteristic was calculated through the Microsoft Excel, using the function NORMINV (0,05; 0; 1).…”
Section: Shs Web Of Conferences 39 01010 (2017) Doi: 101051/shsconfmentioning
confidence: 99%